Intraregional trade and the missing globalization puzzle - Jošić, Hrvoje; Žmuk, Berislav (Oeconomica Jadertina, 2021)
Globalization has led to the lowering transportation costs and the expansion of international trade. However, there is evidence of failure in declining trade-related costs as represented through the rising distance coefficient in the standard gravity model. The importance of intraregional trade for the explanation of the globalization puzzle is highlighted in this paper. A panel regression model was constructed using bilateral trade data for EU-15 countries’ imports in the period from the 2001 to 2018. The random effects model was chosen as the most appropriate model considering the time-invariant characteristics of data. The distance effect is presented with the distance variable defined as a distance between trading partner countries’ capital cities. Additional dummy variables included in the analysis are adjacency, the EU-15 dummy and the continent dummy. The results of the analysis have shown that the missing globalization puzzle still applies. Specifically, the values of the regression coefficient of the distance variable in the observed period have grown both for the overall panel model and the individual countries models. Furthermore, the value of the regression coefficient strongly depends on the used sample. For example, when only trade flows in the range of the first 1000 km are observed, the values of the regression coefficient of the distance variable are very large, implying a rising distance effect.
Keywords: globalization; intraregional trade; distance puzzle; panel-regression modelling